Gerakan Kampus Bersih Narkoba (Bersinar) Melalui Kegiatan Pemeriksaan Urine Pada Mahasiswa Di Wilayah Pesisir - Diniarti, Fiya; Marlianto, Nuche; Hanasti, Novia (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Drug abuse remains a serious problem threatening the younger generation, including university students. The coastal areas of Bengkulu City are vulnerable to drug trafficking due to social and geographical factors. Universities, as educational institutions, have a strategic role in efforts to prevent drug abuse through promotional and preventive activities. This activity aims to detect early drug abuse among students of the Faculty of Health Sciences at Dehasen University Bengkulu, as well as to raise awareness and commitment of the academic community in creating a campus environment free from drugs. The methods for implementing this community service activity include socialization about the dangers of drug abuse, education on the importance of early detection, and urine testing for students of Fikes Dehasen Bengkulu.Urine tests are carried out according to standard procedures using rapid drug test kits. This activity is conducted in a coordinated manner involving lecturers, healthcare workers from the Bengkulu City National Narcotics Agency (BNN), and students as participants totaling 70 people.The results of the activity indicate that out of 70 people who underwent urine testing (early detection), negative results (-) were obtained, which shows that the majority of Fikes Dehasen Bengkulu students are free from drug abuse. The results of education and awareness-raising activities based on the pre-test and post-test show an increase in participants' understanding of the dangers and types of drugs, with the average pre-test score being 62 and an increase in participants' knowledge to an average post-test score of 82.Conclusion: the community service activity of the campus drug-free movement (Bersinar) through urine testing on students of Fikes Dehasen Bengkulu ran smoothly and provided positive benefits for the participants.This activity is effective in supporting efforts to prevent drug abuse and strengthening the commitment of the academic community to creating a healthy, safe, and drug-free campus. Similar activities are recommended to be carried out continuously as part of promotive and preventive programs in higher education institutions.